SEMANTIC RELEVANCE: SYNONYMOUS. BENEFICIAL SIDES OF APPLYING SYNONYMS IN WRITING - Matkarimova, Shokhista; Siddikova , Shakhnoza Khasanboy kizi (Educational Research in Universal Sciences, 2023)
The article discusses issues related to the criteria for determining synonymy language and the formation of syntactic synonyms in sentences and their classification.